Model Loyalitas Pasien Berbasis Kualitas Pelayanan Rumah Sakit Islam di Semarang - Muh. Abdurrouf; Dyah Wiji Puspitasari (Politeknik Kesehatan Tanjung Karang, 2017)
Patient loyalty is very influential on the sustainability of the hospital. The loyalty of the patient is influenced by the patient's satisfaction with the overall service quality in which the satisfied patient returns to the service, and recommends to others. The purpose of this study was to analyze patient loyalty and develop models of patient loyalty improvement based on hospital service quality. The subjects of this study were inpatient at Islamic Hospital in Semarang area, sampling technique used was purposive sampling with 100 respondents. This research method was analytic survey method using cross-sectional approach. Data analysis techniques in this study used The Structural Equation Modeling (SEM) of AMOS 5.0 software package. The results of this study were nursing service, operational service, service quality, positively correlated with patient loyalty and showed a significant relationship. Medical services were positively associated with patient loyalty and show an insignificant relationship. Sex was positively related to medical services, but it did not show a significant relationship, while the relationship between sex with nursing services, operational services, overall service quality and patient loyalty did not significantly relate. The implications of this study can be a reference in improving the quality of services in hospitals so that patient loyalty to the hospital.